Transformational Leadership in Globalization towards Sustainable Development - สัทธาฉัตรมงคล นุช; ธรรมไพบูลย์ อรรถพล (Business Administration and Management Journal Review, 2016)
Since our world has changed in its context affecting the economy and society relative to globalization, leadership of organizations are facing the challenges of coping up with these changes. Leadership of organizations have not been equipped with the proper tools to undertake an unstructured form of change. It is relevant that organization leadership must be aware of the dynamics of change. During the past decade, many studies have focused on leadership forms, such as change-creating leadership or transformational leadership, that are suited for the present situation. Transformational leadership has some characteristics and behaviors that can affect people in the organization and can make a change of the organization. Change-creating leadership has a significant impact on organization success and can lead to a better position in a changing situation. This article discusses John P. Kotter and Kurt Lewin’s topic: “how to change the organization and how to manage change.” Transformational leadership is one of the key elements to support organizational change effectively. Transformational leadership can adopt the philosophy of sufficiency economy to be a practical guideline. Orgnization leadership must have the responsibility to maintain a balance of strategic development and implementation of the organization in order to create sustainable development.